Some aspects of the biology and fishery of Panulirus ornatus fabricius 1798 off Zamboanga, Philippines - Lasola, Ninnette T. (College of Fisheries, University of the Philippines, 1994)
A total of 1233 Panulirusornatus were caught by bottom set gillnet from Labuan and Limpapa, the two study areas sampled and monitored from March, 1988 to February, 1989. There was no significant difference between the catch rates in the two sampling sites. The lobster fishery showed distinct seasonality during the one-year sampling period, showing single peak from October to March. Catches began t decline in April-June period and regular sampling activities conducted from July to September confirmed unavailability of P. ornatus. The data collected were supplemented by information obtained from record of fish dealers (brokers).The fishing gear used was highly size and sex selective. The size of lobsters caught ranged from 74-114 mm CL. Consequently, length-weight relationship were not conclusive.. However, the sizes of lobsters caught in Labuan were bigger than those caught in Limpapa despite the use of gears with the same specifications. This is however, not an indication that there are more thanone population of lobster in the area. This might be due to possible differences in available shelters and habitats between the two sites, migratory behavior of resident lobster in eachsite, or both. The sex ratio is biased in favor of males (1:0.25) but this may also be attributed to behavioral differences between the sexes, migration habits and reproductive activities. Only 6 berried females were caught and their estimated egg production are presented and comparedto other studies. The size of P. ornatus werepositively correlated with depth of capture. However, high abundance appeared to be limited to an intermediate depth (100-180m). Temperature showed no correlation with lobster abundance while salinity readings werealmost constant during the study. The socio-economic profile of fishermen in the study sites is also presented and the contribution of lobster fishing to their total income is discussed.